2019
DOI: 10.1186/s12859-019-2798-1
|View full text |Cite
|
Sign up to set email alerts
|

WASABI: a dynamic iterative framework for gene regulatory network inference

Abstract: Background Inference of gene regulatory networks from gene expression data has been a long-standing and notoriously difficult task in systems biology. Recently, single-cell transcriptomic data have been massively used for gene regulatory network inference, with both successes and limitations. Results In the present work we propose an iterative algorithm called WASABI, dedicated to inferring a causal dynamical network from time-stamped single-cell data, which tackles som… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 68 publications
1
53
0
Order By: Relevance
“…Although more GRN methods for single-cell analysis have been published, we select only those that have available and executable software. Tools that are not accessible by the research communities are excluded from this survey, including ACTION [ 49 ], WASABI [ 50 ] and some others [ 51 , 52 ]. In Table 1 , we show the tools’ available hyperlink, programming language, software interface (graphic user interface, command line or executable scripts), references to their original articles, number of citations, license and rating for overall usability.…”
Section: Implementation and Usabilitymentioning
confidence: 99%
“…Although more GRN methods for single-cell analysis have been published, we select only those that have available and executable software. Tools that are not accessible by the research communities are excluded from this survey, including ACTION [ 49 ], WASABI [ 50 ] and some others [ 51 , 52 ]. In Table 1 , we show the tools’ available hyperlink, programming language, software interface (graphic user interface, command line or executable scripts), references to their original articles, number of citations, license and rating for overall usability.…”
Section: Implementation and Usabilitymentioning
confidence: 99%
“…Typically regulators consist of transcription factors (TFs),genes, RNA binding proteins, and regulator RNAs that can control the gene expression of the target genes [50][51][52]. GRNs govern the decision-making process in response to endogenous and external stimuli; thus, understanding their behavior at the genomic level can give us critical insights into achieving desirable phenotypical traits like increased lysine content [53,54].…”
Section: Methodsmentioning
confidence: 99%
“…Partially-Observed Boolean Dynamical System (POBDS) is a class of hidden Markov model (HMM) with Boolean state variables which has been the subject of attention in recent years, especially in Genomic Signal Processing [1][2][3][4]. Many recent findings have shown that the POBDSs is capable of simulating the dynamical sequence of protein activation patterns of gene regulatory networks (GRNs) [5][6][7][8]. Several tools are designed for this signal model in recent years, including the Boolean Kalman filter (BKF) [9,10] and the Boolean Kalman smoother (BKS) [10,11], which are recursive minimum mean-square error (MMSE) estimators of the state of a POBDS when all system's parameters are known.…”
Section: Introductionmentioning
confidence: 99%